Agroecology: the "way" for rural sustainable development in the process of rural extension - Azevedo, Leticia Fatima de; Netto, Tatiane Almeida (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper presents an analysis as the centerpiece of texts authored by Hecht (1999); Norgaard and Sikor (1999); Guzman Casado, Gonzalez De Molina and Sevilla Guzman (2000); Caporal and Costabeber (2000; 2002) and; Costa Gomes and Borba (2004), seeking to report the importance of agroecology as promising sustainable rural development, and acting as a framework for a new proposal for extension in Rio Grande do Sul (RS) state. It is through agroecology we can legitimize sustainable rural development, seeking harmony between the various dimensions of sustainability. Acting in this way, as a science or scientific discipline, agroecology seeks the transition from the current development model to a more sustainable and equitable, with the central axis recognition of "knowledge" of farmers and their families, caring for your side social, cultural and not only with the economic side (production and productivity). Demand for another style or model of agriculture must incorporate principles, methods and ecologically-based technologies.